PENGARUH CORPORATE GOVERNANCE DAN KUALITAS AUDITOR EKSTERNAL TERHADAP MANAJEMEN PAJAK - Yunika Dewi Lestari; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2016)
The aim of this study is to examine the influence of  corporate governance and quality of external auditor quality on  tax management of the company. Independent variable used in this study are corporate governance which is measured by proxies of number of commissioner, percentage of independent commissioner, compensation of board of commissioner and board of directors while external auditor quality which is proxied by size of public accountant firm. Dependent variable is tax management which is measured by effective tax rate (ETR) The population used in this study consist of manufacture firms listed on the Indonesia Stock Exchange in 2009-2014. The sampling method used in this study is purposive sampling and obtained 29 companies. This study uses multiple regression analysis for hypotheses testing. The results of this study showed that number of commissioner has negative effect on tax management measured by tax expense but has positive effect on tax management measured by cash tax paid, percentage of independent commissioner has no effect on tax management measured by tax expense but has negative effect on tax management measured by cash paid, compensation of board commissioner and directors has no effect on tax management measured by tax expense but has negative effect on tax management measured by cash paid, external auditor quality has no negative influence on tax management measured by tax expense and has no influence on tax management measured by cash paid.